ULAMA MELAYU PADA ABAD XX STUDI ATAS KARYA-KARYA ULAMA MELAYU SUMATERA SELATAN - Aliasan Aliasan (Wardah, 2018)
Abstract: At the beginning of the 20th century, especially after Indonesia's independence, the production of Middle Eastern intellectual traditions in South Sumatra declined, because the contact of the Archipelago, especially the Malays of South Sumatra with the Middle East was no longer intensive. This has caused changes in the style aspects, themes, forms and characteristics of the works of the Malay scholars of South Sumatra. This process certainly does not take place in a simple manner, but is complex. Because, in the 20th century, Indonesia has become independent, science has developed, technology has become more sophisticated, information has become global and easily accessible. Because of this, contact between the Middle East and South Sumatra Malays should be more intensive. However, the fact is the opposite. The complexity of the changes and developments in the works of the 20th century Malay ulama of South Sumatra was a very significant problem to be discussed in order to know and construct the motifs, patterns, themes, forms, characteristics, and influence of the works of the South Sumatra Malay Ulama in the century 20th. The themes contained in the works of the Malay ulama of South Sumatra in the twentieth century consisted of philosophical issues, life views, values and ethics, science, ethos work, spirituality, ethics and systems of government, social order, Islamic history, law- Islamic law. The forms of the works of the Malay ulama of South Sumatra in the twentieth century AD consisted of a yellow book, in the form of a religious book. The style consists of Sufism, historical patterns, theological or monotheistic patterns, scholarly patterns, adab, laws, morals, benefits and wisdom, history, social life, entertaining, and solace. Keyword: Malay Ulama, South Sumatera.